(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Mechanical soft reduction (MSR) is an effective method to eliminate the centerline segregation and porosity of the continuous casting steel, and the reduction amount is a key parameter that determines whether the MSR could be applied successfully. In the present work, a 2D heat transfer model was developed for predicting the non-uniform solidification of the wide-thick slab. The measured shell thickness by nail shooting experiment and the measured slab surface temperature by infrared camera were applied to validate the 2D heat transfer model. A new calculation method of theoretical reduction amount that could consider the influence of non-uniform solidification of the wide-thick slab was then derived. Based on the predicted temperature field by the 2D heat transfer model and the newly-proposed calculation method, the required theoretical reduction amount and reduction gradient/rate for the wide-thick slab were calculated and discussed. The difference between the newly-proposed method and the previous method, the influence of the casting speed and slab thickness on the required theoretical reduction amount and reduction gradient/rate were also investigated.